Polysiloxane-Multiwalled Carbon Nanotube Layers on Steel Substrate: Microstructural, Structural and Electrochemical Studies. Issue 13 (12th September 2019) - Gawęda, M.; Długoń, E.; Sowa, M.; Jeleń, P.; Marchewka, J.; Bik, M.; Mroczka, K.; Bezkosty, P.; Kusz, K.; Simka, W.; Błażewicz, M.; Sitarz, M.
Abstract : The study involved research on two types of nanocomposite coatings based on polysiloxane and multiwalled carbon nanotubes (MWCNTs). The coatings were made using the same steel substrate while they were obtained by two different methods: sequential and co-deposition method. Spectroscopic measurements using Raman and infrared spectroscopy, as well as microscopic examination and wettability tests, were applied to examine structure, microstructure and physical properties of the obtained layers. Electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP) were used to characterize the coatings from the point of view of their corrosion resistance. The Raman confocal spectroscopy provided valuable data explaining the behavior of carbon nanotubes in the polymer matrix and allowed to distinguish structural differences in the two analyzed layers. The results obtained for nanocomposite coatings were compared with the results obtained for coatings made on the basis of their individual components, namely the coating consisting of pure carbon nanotubes as well as those obtained from pure polysiloxane. Based on the applied methods, an attempt to explain the differences in the corrosion resistance of four types of coatings was made.